2022
DOI: 10.1002/jmr.2985
|View full text |Cite
|
Sign up to set email alerts
|

Study on the interaction mechanism between luteoloside and xanthine oxidase by multi‐spectroscopic and molecular docking methods

Abstract: Gout is an inflammatory joint disease caused by urate crystal deposition, which is associated with hyperuricemia. Gout will take place when the uric acid accumulates. Xanthine oxidase (XO) is a crucial enzyme in the formation of uric acid. Inhibiting XO is one of the means to ameliorate gout. Luteoloside is a kind of natural flavonoid, which has an excellent prospect for relieving gout. But there are few reports on the interaction mechanism between luteoloside and XO currently. In this study, the interaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…13 The far UV-CD spectra were used to investigate the dynamics, interaction, and folding of proteins and to measure the helical content. To study the effect of TND (10,20, and 40 μM) on proteins (BSA/HSA) conformational change, the characteristic alpha-helical peaks (at 208 and 222 nm)…”
Section: Circular Dichroism (Cd)mentioning
confidence: 99%
See 2 more Smart Citations
“…13 The far UV-CD spectra were used to investigate the dynamics, interaction, and folding of proteins and to measure the helical content. To study the effect of TND (10,20, and 40 μM) on proteins (BSA/HSA) conformational change, the characteristic alpha-helical peaks (at 208 and 222 nm)…”
Section: Circular Dichroism (Cd)mentioning
confidence: 99%
“…For getting a better perspective of protein interactions with molecules, spectroscopic and computational analyses are widely employed. Enzyme xanthine oxidase and the flavonoid luteoloside binding was studied by Chen et al, employing multi‐spectroscopic and the molecular docking method 20 . The transport proteins, serum albumins, HSA and BSA, are also explored for their interactions with drugs and other molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It mainly binds to residues in the active site pocket of XO (including Glu802, Leu873, Phe914, Arg880, Phe1009, Thr1010, Val1011, Leu1014, and Pro1076) through hydrophobic interactions, thereby altering the microenvironment and secondary structure of XO and reducing its catalytic activity (Pauff & Hille, 2009;Yan et al, 2013). Chen, Luo et al (2022), Chen, Zhu et al (2022), andChen, Wang et al (2022) reported that luteoloside, a derivative of luteolin, also inhibited XO activity; the luteoloside-XO interaction was spontaneous and, like luteolin, luteoloside inhibited the activity of XO by altering the secondary structure of XO (increasing the contents of β-sheets and β-turn, and decreasing the α-helix content of XO), besides enhancing the hydrophobicity of XO by forming hydrogen bonds and hydrophobic forces. By contrast, 6-hydroxyluteolin interacts with XO by electrostatic interaction forces (π-π T-shaped bond) and hydrogen bonds and shows high affinity for the binding site of XO (Cheng et al, 2015).…”
Section: In Vitro Structure-activity Relationship Analysis Of Flavonesmentioning
confidence: 99%
“…Rasoulzadeh et al (2009) mainly reviewed the interaction between plant flavonoids (mixtures) and molybdenum hydroxylases (XO and aldehyde oxidase). In addition, the role of some foods with a high content of flavonoids (e.g., tea and grapes) in XO inhibition and treatment of HUA has also been reviewed (Chen, Luo, et al, 2022;Chen, Zhu, et al, 2022;Chen, Wang, et al, 2022;Dwibedi et al, 2022;Feng, Ou et al, 2022;Mehmood et al, 2019). However, to our knowledge, the mechanism by which pure flavonoids exert their anti-hyperuricemic effects by the modulation of XO activity in light of both in vitro and in vivo has not been reviewed from the structure-activity relationship and animal experiments.…”
Section: Introductionmentioning
confidence: 99%